What Is a “Good Death” for an Animal? Review of Jocelyne Porcher, Pour une Mort Digne des Animaux - Sax, Boria (Humanimalia, 2015)
Jocelyne Porcher, Pour une mort digne des animaux. Introduction by Elisabeth de Fontenay. Paris: Éditions du Palais, 2014. 107 pp. € 14.50.